2009
DOI: 10.1111/j.1469-7998.2008.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambush site selection and ontogenetic shifts in foraging strategy in a semi‐aquatic pit viper, the Eastern cottonmouth

Abstract: Although habitat selection has been studied in a variety of snake taxa, little is known about habitat selection in aquatic snake species. Additionally, due to their small size and secretive nature, juvenile snakes are seldom included in habitat selection studies. The Eastern cottonmouth Agkistrodon piscivorus is a semiaquatic pit viper known to use ambush, sit-and-wait foraging strategies. Ambush hunters are likely to select habitats that increase opportunity for successful prey capture while minimizing predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…Selection of foraging sites is the product of a trade-off driven by food availability and the cost, or perceived cost, concomitant with those sites (Werner et al 1983;Lima and Dill 1990;Schalk et al 2010;Eskew et al 2009). In this study, we observed an ontogenetic niche shift in the form of ambush-site selection, between metamorphs and adults of C. cranwelli.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Selection of foraging sites is the product of a trade-off driven by food availability and the cost, or perceived cost, concomitant with those sites (Werner et al 1983;Lima and Dill 1990;Schalk et al 2010;Eskew et al 2009). In this study, we observed an ontogenetic niche shift in the form of ambush-site selection, between metamorphs and adults of C. cranwelli.…”
Section: Discussionmentioning
confidence: 56%
“…The selection of habitat sites by an individual is a product of many interacting factors, including morphological and physiological constraints. Patterns of habitat selection by individuals reflect access to resources (e.g., food), risks of competition and predation, and any number of ecophysiological factors (Eskew et al 2009;Schalk et al 2010). As body size increases during ontogeny, importance and strengths of these interacting factors shift, resulting in the ability of individuals to use different habitats and food resources.…”
Section: Introductionmentioning
confidence: 99%
“…However, a more intensive study employing different capture methods at one fishless wetland suggested that Ag. piscivorus also feeds heavily on Ambystoma in those habitats (Eskew, Willson & Winne, 2009).…”
Section: Snake Dietsmentioning
confidence: 99%
“…The predator must avoid detection (Bailey, 1986;Kral et al, 2000;Bilcke et al, 2006;Eskew et al, 2009), attain high accelerations and speeds (Cooper et al, 1985;Alfaro, 2002;reviewed in McBrayer and Wylie, 2009), and retain some control over strike kinematics (van Leeuwen et al, 2000;Deban et al, 2001). To achieve these goals, ambush predators use three strategies to capture prey: (1) concealment through burrows or camouflage, (2) quick traverse of a potentially large distance to prey and (3) rapid attack to impact prey before escape.…”
Section: Introductionmentioning
confidence: 99%